Eksplorasi Hubungan Antara Seni, Musik, dan Bentuk Ekspresi Kreatif dalam Ibadah Kristen Masa Kini - Thusiapratama, Gabriel Levi; Santo, Joseph Christ (Sekolah Tinggi Teologi Berita Hidup, 2025)
With developments in various aspects that continue to accelerate due to the influence of globalization, Christian worship is also experiencing transformation. Today's Christian worship involves various relationships between art, music, and other forms of creative expression which are packaged in such a way that it becomes Contemporary Worship. However, the use of art and creative expression in Christian worship does not always run smoothly. Today's Christian worship raises several issues including those related to the congregation's spiritual experience with contemporary worship packaging, challenges, and debates regarding the limits of the use of art in the context of worship, but some opportunities can be found from the existence of today's Christian Worship, as well as the relationship between the use of art in the context of worship. art in worship with increased congregational participation. The research method used is a literature review method that focuses on collecting and analyzing various literature relevant to exploring the relationship between art, music, and forms of creative expression in contemporary Christian worship. This research concludes that art, music, and different forms of creative expression have quite a large influence and need to receive attention in modern Christian worship. Keywords: art; music; creative expression; contemporary Christian worship